O ensino de arte nas escolas públicas paulistas : contraponto crítico sobre a discrepância entre o que se aspira e o que se ensina - Vieira, Leandro Augusto Gonçalves (Universidade Federal de São Carlos, 2016)
Considering the theoretical and metodological aproaches of Critical Theory of Society, especially by the contributions of Adorno and Horkheimer, this study analyses the discrepancy between what is yearned for and what is taught about art in the public school of São Paulo State. One can verify the misunderstanding of negative dialectic tension between autonomy and adaptation that are carried and expressed in a fundamental educative principle which conciliates the citzenship exercise and the development of job skills. This lack of understanding becomes the formative practices unable to disrupt the collapse of culture. In this Master Thesis, the aim is to demonstrate, by the critical conception of aesthetic experience, the recovering of Art as an underlying element for the formation of learner's emancipation.
Keywords: Arte; Dialética negativa; Emancipação; Art; Negative dialectics; Emancipation; CIENCIAS HUMANAS::EDUCACAO